Difficulties Encountered by the Students in Learning Mathematics - Arsad A. Radiamoda (Indonesian Journal of Educational Research and Technology, 2024)
The study looked into the difficulties encountered by the students in the learning of Mathematics among freshmen of Adiong Memorial Polytechnic State College-Laboratory High School in Ditsa-an Ramain, Lanao del Sur. This study prepared the questionnaire for first-year high school students. The data gathered were tabulated, analyzed, and interpreted using the frequency and percentage distribution and the weighted mean. It was found that the instruction and teacher/teaching methodologies ranked as the main cause of the difficulties encountered by the students in learning Mathematics. In the light of the findings, conclusion, and implications of the study the following recommendations are given: (a) teachers in Mathematics must be able to check the kind of instruction and methodologies they were applying to their students; (b) parents should give their full support to their children. This can be done by coordinating and cooperating with the school where their children are studying; (c) school administrators must observe the teacher at least every grading so that they know their standing in terms of teaching; and (d) future researchers should conduct on the same study but of different coverage and different subject.